2005
DOI: 10.1111/j.1553-2712.2005.tb01486.x
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of Residency Programs' Web Sites Important to Student Applicants

Abstract: Objectives: To determine which components of a residency Web site (RWS) are important to residency applicants. Methods: The authors performed a cross-sectional observational study of residency applicants. All applicants were invited to participate and were provided with a nine-question survey. Applicants were asked questions regarding the importance and impact of RWSs on the residency application process. They were also asked to rate items regarding content and aesthetics, and then rank all items in order of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
174
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(176 citation statements)
references
References 10 publications
(11 reference statements)
2
174
0
Order By: Relevance
“…They also reported that reported that 41% of applicants reported not applying to at least one residency program secondary to poor website quality (2). In another study, Mahler et al also reported that website accessibility and ease of navigation were important criteria in the decision-making process for 40% of emergency medicine applicants (3).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…They also reported that reported that 41% of applicants reported not applying to at least one residency program secondary to poor website quality (2). In another study, Mahler et al also reported that website accessibility and ease of navigation were important criteria in the decision-making process for 40% of emergency medicine applicants (3).…”
Section: Introductionmentioning
confidence: 95%
“…Previous studies have demonstrated that amongst anesthesia and emergency medicine residency applicants, the content of the program's website influences a prospective applicant's decision to apply to the program in 56% and 78%, respectively (1, 2). Specifically, Gaeta et al reported that emergency medicine residency applicants were most interested in information regarding the residency curriculum, hospital, faculty, current residents, and research opportunities in a survey-based study (2).…”
Section: Introductionmentioning
confidence: 99%
“…In 2005, Gaeta et al studied the aspects of a web site that were important to fourth year medical students applying to a single residency program (2). They found that the information provided on a residency program's web site did influence a candidate's decision about applying to that program.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, in that study, 41% of residents reported not applying to at least one residency program based on the poor quality of the associated Web site. 2 Finally, Mahler et al 3 reported that almost all emergency medicine applicants research programs online and 40% considered an easily navigated Web site important in the decision-making process. In conclusion, these studies demonstrate that the information available on and the accessibility of residency program Web sites are important factors in the decision-making process of residency applicants.…”
mentioning
confidence: 98%